Study of Serum Surfactant Protein D Levels in Chronic Obstructive Pulmonary Disease Patients - Surya Tiwari; Durain Fatima; Pravin S. Gowardipe (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2023)
Background: An increasing prevalence of chronic obstructive pulmonary disease (COPD) worldwide is one of the major reasons for morbidity and mortality. Surfactant protein D (SP-D) has been identified to have a role in the host defence system of the lungs and regulation of surfactant homeostasis. SP-D is considered as a biomarker of ascertaining the severity of COPD and risk of future exacerbations. Objectives: This study aimed to investigate changes in lung functions and SP-D levels in COPD patients for early diagnosis and timely intervention to prevent progression of the disease. Methods: One hundred stable COPD patients were enrolled for the study and were compared to 100 normal healthy individuals of the same age. Those fulfilling the inclusion and exclusion criteria were enrolled for the study. Pulmonary function tests were performed via spirometry. Blood samples were collected and estimation of SP-D was done using enzyme-linked immunosorbent assay (ELISA). Results: The observation revealed a significant decline in ventilatory functions with increasing severity of COPD, as reflected by the decrease in FEV1% and FEV1-to-FVC ratio compared to controls (P < 0.001). Serum SP-D levels were significantly increased in COPD patients (P < 0.001) compared to controls. Conclusion: SP-D estimation in COPD patients helps in monitoring the progression and prognosis of the diseases; formulate strategies for early therapeutic intervention to prevent risk of exacerbations to improve quality of life.